Study of Water Chemical Compounds at Geothermal Area: Case on Geothermal Weh Island, Jaboi - Evi Yufita; Muhammad Isa; Aztarina Ermy Vijaya (Journal of Aceh Physics Society, 2020)
Kandungan senyawa kimia air sangat berguna dalam penentuan karakteristik fluida panas bumi terutama sumbernya dan arah aliran fluida tersebut. Oleh karena itu dilakukan penelitian untuk mengkaji senyawa kimia air yang terkandung pada lapangan panas bumi. Penelitian ini dilakukan dengan metode Titrasi dan Spektrofotometer Serapan Atom (SSA). Pengambilan sampel air dilakukan di dua lokasi mata air panas. Untuk pengujian sampel dilakukan pada Balai Riset dan Standarisasi (Baristan) Banda Aceh. Pengolahan data dilakukan dengan perbandingan kandungan kimia air, sedangkan interpretasi menggunakan diagram segitiga Ternary. Diagram segitiga ini meliputi Cl-SO4-HCO3, digunakan untuk mengetahui kandungan fuida panas bumi, Cl-Li-B digunakan untuk menentukan temperatur suatu lokasi panasbumi dan Na-K-Mg untuk mengetahui kesetimbangan lingkungan fluida panas bumi. Hasil analisis senyawa kimia air menunjukkan bahwa fluida panas bumi memiliki konsentrasi yang didominasi sulfat SO4,  Adapun nilai konsentrasi sulfat masing-masing 95% sampel I dan 97% sampel II. Kandungan kimia air ini diperkirakan berada pada zona upflow. Fluida panas bumi yang muncul ke permukaan dari dua lokasi sampel bersumber langsung dari aktivitas magma. An analysis of the flow of geothermal fluid has been carried out in the Jaboi geothermal field, Sabang. This study aims to obtain a zone of geothermal fluid flow in relation to faults/faults. This research was conducted by the titration method and Atomic Absorption Spectrophotometer (AAS). Sampling was carried out at two hot spring locations, namely crater I and crater IV. For sample testing carried out in a standardized laboratory. Data processing is done through comparison of chemical fluid content and interpretation of Ternary triangle diagrams. The triangle diagram includes Cl-SO4-HCO3, Cl-Li-B and Na-K-Mg to determine the characteristics of geothermal fluids. Based on data that has been processed and correlated with other supporting data (local geological conditions, magnetic, and temperature) shows a relationship that affects each other with the presence of faults. The analysis shows that geothermal fluid in the upflow zone is characterized by a dominant SO4 sulfate concentration (95% for sample I and 97% for sample II). In the Na-K-Mg triangle diagram, the fluid shows an immature water condition because the fluid has mixed with meteoric water. Based on the analysis of the geochemical data of the study area, it was shown that there is a connection with Ceunohot fault trending northeast to southwest as the controller of the flow of geothermal fluid.Keywords: Ternary triangle diagrams, geothermal fluid, chemical water compounds